WHAT EXPLAINS CITIES’ CLIMATE POLICY - MAKING? A REVIEW OF DRIVERS AND BARRIERS - SIPPEL, Maike; JENSSEN, Till (Journal of Environmental Management and Tourism, 2010)
A large proportion of greenhouse gas emissions is produced in urban areas. Therefore, local mitigation policies have to play an important role in any effective global climate protection strategy. Based upon a literature review, this article gives an overview of drivers and barriers for local climate governance. Drivers and barriers fall into broad categories like ‘economic’, ‘informational’, ‘institutional/legal’, ‘liveability’ or ‘political/cultural’. Understanding drivers and barriers of local climate governance may support cities in developing appropriate local climate action plans. It may also inform other policy levels to help realize the local climate protection potential. For many cities, cost savings are a primary driver for local mitigation policies. The collective action problem associated to climate protection and inappropriate legal frameworks are key barriers. We conclude that in the absence of proper regulatory frameworks, cities could focus on ‘no-regret’ measures and demonstration projects. Local co-benefits need to continue in their role as door openers for local mitigation. The trend towards adaptation can support local mitigation activities, as it raises awareness for a city’s vulnerability to climate change. Finally, collective action and effective legal frameworks from the global through to the local level are considered to be essential for effective local mitigation activities.